2020
DOI: 10.1186/s12870-020-02450-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome profiling reveals cold stress responsiveness in two contrasting Chinese jujube cultivars

Abstract: Background: Low temperature is a major factor influencing the growth and development of Chinese jujube (Ziziphus jujuba Mill.) in cold winter and spring. Little is known about the molecular mechanisms enabling jujube to cope with different freezing stress conditions. To elucidate the freezing-related molecular mechanism, we conducted comparative transcriptome analysis between 'Dongzao' (low freezing tolerance cultivar) and 'Jinsixiaozao' (high freezing tolerance cultivar) using RNA-Seq. Results: More than 20,0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 72 publications
3
12
0
Order By: Relevance
“…In this study, 147 TFs belonging to 32 TF families, including AP2/ERF (27), MYB (19), bHLH (13), WRKY (21), C 2 H 2 (8), and NAC (13), were largely regulated by cold stress (Table 2, Figure 5). Similar to our findings, in previous studies, comparative transcriptome analysis of rice, Chinese jujube, and peanut under cold stress conditions identified the above TF families to be the most regulated gene members [60,61,71,72]. These TF genes in their respective families are divided into diverse subgroups based on their specific motif structures, showing that they may perform their specific biological activities under cold stress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, 147 TFs belonging to 32 TF families, including AP2/ERF (27), MYB (19), bHLH (13), WRKY (21), C 2 H 2 (8), and NAC (13), were largely regulated by cold stress (Table 2, Figure 5). Similar to our findings, in previous studies, comparative transcriptome analysis of rice, Chinese jujube, and peanut under cold stress conditions identified the above TF families to be the most regulated gene members [60,61,71,72]. These TF genes in their respective families are divided into diverse subgroups based on their specific motif structures, showing that they may perform their specific biological activities under cold stress.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 14 DEGs encoding MAPKs were regulated by cold stress (Table S4). Multiple MAPKs have been implicated in improving cold tolerance in rice and Chinese jujube, according to previous research [60,61]. In this study, RBOH (Zm00001d009248), MAP3 (Zm00001d001978), and MKK3 (Zm00001d013510 and Zm00001d028026) had higher expression levels in the tolerant lines (Table S4).…”
Section: Discussionsupporting
confidence: 55%
“…In the present study, there were more downregulated genes than upregulated genes at 4 °C and − 20 °C in R. xanthina f. spontanea . This result is similar with those of Kou et al [ 22 ] in potato and Zhou et al [ 23 ] in Chinese jujube, which indicated that different cultivars may have similar responses and cold resistance mechanisms. However, these results are not consistent with those of Niu et al [ 24 ] in Prunus persica under freezing stress treatment, in which the number of upregulated genes was greater than that of downregulated genes.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, researchers have comprehensively analysed gene functions and metabolic pathways at the transcriptional level under cold stress using RNA-seq technology [ 9 , 11 , 12 ]. Recent plant transcriptome studies have found that calcium ion (Ca 2+ ) and reactive oxygen species (ROS) mediated signalling pathways and mitogen activated protein kinase (MAPK) cascades in plants are able to rapidly respond to cold stress [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%